PEMANFAATAN TULANG IKAN TUNA SEBAGAI UPAYA PENGURANGAN LIMBAH MENJADI OLAHAN KERIPIK PADA UMKM MARIFA - Ermawati, Sri; Karlan, Lalu Agus (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2024)
One of the snacks is tuna bone chips, which consists of thin round slices made from tapioca flour. The use of materials made from fish bones is intended to reduce the waste of tuna fish bones that are discarded. This service activity was conducted in Malaju Village, a hamlet in the western part of Paropa, where most residents work as entrepreneurs concentrating on processed fish products. Among the most discarded waste from fish production is fish bones. This waste can pollute the surrounding environment. The purpose of this service is to help MSME players find solutions so that production waste does not pollute the surrounding environment. This service uses evaluation, socialization, and training. The result of utilizing tuna fish bones for making chips is to reduce the amount of tuna fish bone waste and make this product an additional source of income for small and medium businesses (MSMEs).